2021
DOI: 10.1186/s12902-021-00833-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and its components are associated with thyroid volume in adolescents

Abstract: Objective To explore the association between metabolic syndrome (MetS) and its component and thyroid volume in Chinese adolescents, and to compare the detection rate of MetS under the three different diagnostic criteria. Methods A total of 1097 school students (610 males and 487 females, ages 12–15 years) were enrolled. All the participants underwent physical examination, biochemical test, and thyroid gland ultrasonography. The thyroid volume of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Although sarcopenia has gained much interest in cancer treatment ( 14 ), the correlation between skeletal muscle mass and thyroid volume or function has not yet been demonstrated. Regarding the association between thyroid volume and patient physique, it has been shown that thyroid volume positively correlates with BMI ( 26 ). Consistent with this report, a positive correlation between BMI and RTI was found in this study’s patient cohort (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Although sarcopenia has gained much interest in cancer treatment ( 14 ), the correlation between skeletal muscle mass and thyroid volume or function has not yet been demonstrated. Regarding the association between thyroid volume and patient physique, it has been shown that thyroid volume positively correlates with BMI ( 26 ). Consistent with this report, a positive correlation between BMI and RTI was found in this study’s patient cohort (data not shown).…”
Section: Discussionmentioning
confidence: 99%